USING OF THE SMART BOARD AS AN INTERACTIVE DEVICE IN ORGANIZATION OF THE ENGLISH LESSONS AT THE 10TH FORM - Vakulchyk, О.О.; Sagan, О.В. (Journal of Information Technologies in Education (ITE), 2013)
The planning of the English Lesson “The Films” in the 10th with the using of the smart board is proposed in the article.